Representasi Konsep Kyouiku Mama dan Pola Asuh Orang Tua pada Tokoh Akari Kudo dalam Film Biri Gyaru - Isnaen Nur Layla Safitri; Yusida Lusiana; Anggita Stovia (Pusat Studi Wanita dan Keluarga UGM, 2023)
This study was conducted to find out the concept of kyouiku mama and parenting style represented by the character Akari Kudo in the film Biri Gyaru. The method used in this study is descriptive qualitative method with a semiotic approach by John Fiske which consists of three levels of analysis is the level of reality, the level of representation, and the level of ideology. This research shows that there is the concept of kyouiku mama which is represented by the character Akari which is illustrated through the appearance and costume codes, expression codes, behavior codes, and environment codes. Meanwhile, at the representation level, it is shown through aspects of the camera code, setting code, and dialogue code. At the ideological level, there is an ideology of feminism and patriarchy in this film. The results of this study indicate the existence of a feminist ideology shown by the character Akari Kudo (mother) through her involvement in every process of children's education, both formal and informal education, as well as through her role in always fighting for her daughter's education. There is also a patriarchal ideology depicted in the character Toru Kudo (father) who always prioritizes his sons' education and ignores his daughters' education. In addition, the parenting style analysis found that there was a authoritative parenting style applied by Akari Kudo (mother) and an authoritarian parenting style by Toru Kudo (father) for their children.